Synthesis, Characterization and Photocatalytic Activity of Tin Oxide Nanocrystals - Sharma, Shatendra; Vats, Monika; Sharma, Jyotsna; Chhabra, Arvind; Kumar, R.K. R.; Chuang, Cheng-Hsin (Current Nanoscience, 2021)
Background: Tin oxide nanoparticles also show good photocatalytic efficiency due to wide bandgap and high recombination rates of photo-generated electron-hole pairs. Being non-toxic and chemically stable, the tin oxide nanoparticles are used as dynamic photo-catalyst for the degradation. Tin oxide nanocrystals suitable for charge storage devices are synthesized using the coprecipitation technique. Objectives: Synthesis of Tin oxide nanocrystals by using the co-precipitation method for photocatalytic activity under sunlight that can be used for photo-degradation. The method of synthesis and characterization are also discussed. Materials and Methods: The nanocrystals are prepared by co-precipitation method using stannic chloride and sodium carbonate. Sodium carbonate is added under constant stirring drop by drop for 90 minutes. The solution is settled for 4 hours. The precipitates are first washed using de-ionized water and then with ethyl alcohol. The dried powder of nanocrystals is then calcinated at 500°C for one hour in a muffle furnace. The structural, morphological, optical, and electrical characterization of these synthesized crystals is done using (XRD), (FESEM), (TEM), (UV-Visible), (FT-Raman), Zeta potential, and dielectric constant measurements. Results and Discussion: The sizes of synthesized nanocrystals vary from 25 nm to 100 nm and are found to be optically transparent. The dielectric constant of nanocrystals is measured in the frequency range of 100Hz-1MHz and it can be seen that it declines from 2000 at a frequency of 100Hz to 30 at 1MHz. However, this decline in dielectric constant with frequency can be explained well on the basis of strong space charge polarization and rotational direction polarization processes in nanostructures. In the high-frequency regions, these processes cannot follow the electrical field frequency variations that result in the rapid decrease of dielectric constant. Photocatalytic Activity: The photocatalytic activity of the particles under sunlight is also investigated, which shows that the crystals show degradation of the methylene blue dye under sunlight irradiation. Theoretical Investigations with DFT: The bandgap of the particles was also calculated from the UV-VIS spectra, which was found to be 3.6 eV and this experimentally observed value of bandgap matches with that calculated theoretically from Density Functional Theory (DFT) using Local Density Approximation (LDA). Conclusion: The method of synthesis reported in the present paper is scalable and can be used for the commercial synthesis of SnO2 nano-crystals for electrodes and energy storage devices.
Keywords: nanocrystals